Unruptured Aneurysm of Sinus of Valsalva Coexisting with the Large Ventricular Septal Defect and Severe Aortic Regurgitation in a Young Man - Pouya Nezafati; Mohammad Hassan Nezafati; Hamid Hoseinikhah (Case Reports in Medicine)
Introduction. Unruptured sinus of valsalva aneurysm (SVA) is a rare congenital anomaly, particularly, when it coexists with a ventricular septal defect (VSD) and aortic regurgitation due to the prolapse of the elongated aortic cusp into the VSD. In this report, we present the case of a 19-year-old young man with VSD challenging in spite of dyspnea and lower limb edema. Presentation of Case. Its diagnosis was made on the basis of transthoracic echocardiography results. Surgical management consisted of replacing the SVA with mechanical valve prosthesis. A Gore-Tex patch repaired the VSD. Discussion. In the follow-up periods, clinical and echocardiographic tests showed that the patient was in excellent status. Conclusion. SVA requires a surgical procedure due to its high risk of mortality in unoperated patients and a good safety of surgery.